Analisa Model Senibina Generik bagi Komponen Perundingan Kandungan dalam Sistem e-Pembelajaran - Siti Salmah, Md Kassim (2006)
E-learning is a variation method in a popularly known online learning. With the advancement in e-learning, it is popularly used among the system developer either in learning or commercial purposes. However, the advancement is not in line with the development of e-learning system that is critical in providing architecture to represent the interaction between the typical components involved in the whole system. This research gives an insight on basic architecture component that involve in the content negotiation process of e-learning. Architectural assessment is conducted to see the needs involved in content negotiation process in e-learning. ATAM method is chosen to analyze the content negotiation needs in e-learning system. The identified quality attributes in this method are the security, functionality, variability, modifiability, performance and reliability. The results of this analysis will help in developing content negotiation process for e-learning system.